Edmonton Eskimos : brand value vs social values? - Brooks, Bradley; Shirley, Britt M. (London : Society for Case Research, 2021)
The Edmonton Eskimos was one of the most successful and popular franchises in the Canadian Football League (CFL), but the team was facing increasing pressure to change its name. Some considered the Eskimos’ nickname disrespectful and racially insensitive to Canada’s Arctic-based native population, but the team feared that changing the team’s name might upset its fan base and risk brand equity. Other professional and college sports teams had faced similar pressure, with some changing their nicknames and others taking no action. The student is asked to consider how a name change might affect its various stakeholders, as well as whether use of the name was cultural appreciation or cultural appropriation. The student then must decide on a recommended course of action going forward regarding this controversy.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Edmonton Eskimos (Football team) -- Management -- Case studies; Social responsibility of business -- Case studies; Branding (Marketing) -- Case studies